(untitled) (Research, Society and Development, 2020)
Military firefighters are subject to situations of tension and rapid response, due to the seriousness of the profession and by work object. The work of firefighters is linked to the countries of the population, exploited by the media through the broadcast of disasters, both natural and man-made. Emergency and disaster situations refer to a situation that goes beyond the condition of emotional stability so discussed among public security professionals. This research aimed to investigate the prevalence of stress in a group of military firefighters in the municipality of Ponta Porã, in the state of Mato Grosso do Sul, Brazil. Sociodemographic questionnaires were used to characterize the studied population and Lipp’s Stress Symptoms Inventory for Adults, which investigates the prevalence of stress and its phases. In total, 33 bombers involved in the study, 3 of which were identified in the resistance phase, in which the individual comes into contact with the stressor, but still remains in some coping attitude, still suggesting a behavior to overcome the stressor object contact. However, despite the fact that the fire department’s emergency service is a requirement for the occurrence of stress and implies the perception of QOL, the firefighters participating in the research showed, in the great majority, a change to overload and peculiarities inherent to the service.